Growth performance and carcass traits of indigenous Nigerian guinea fowl fed on different dietary protein levels - Alabi, Olayinka Olubunmi; Abang, Cyril; Olajide, Olasunkanmi Peter; Animashahun, Rasaq Adekunle; Etta-Oyong, Stephen Otu (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This work examined the results of different dietary protein levels on indigenous Nigerian guinea fowl growth performance and carcass yield. Materials and Methods: One hundred and eight unsexed indigenous keets were randomly assigned to three treatments with experimental diets containing 22%, 24%, and 26% crude protein (CP) in a completely randomized design, with 3 replicates with 12 keets in each replicate. The parameters were measured, including proximate composition, feed intake, growth rate, feed conversion ratio (FCR), and carcass yield. Results: The birds fed diets containing 24% CP gained the most body weight at 619.83 gm and had the highest FCR of 3.45. The presence of CP had an impact that was significant (p < 0.05) on most carcass traits and prime cuts but not on gastrointestinal tract weight, head weight, dress percentage, or organ yield. Conclusion: The study concluded that the dietary CP level of 24% was optimal for body weight gain and carcass yield. J. Adv. Vet. Anim. Res., 10(3): 403–409, September 2023 http://doi.org/10.5455/javar.2023.j693